CASE STUDY: USE OF LOCAL NETWORK SYSTEM IN PT.UNITEK DRIVINDO - Syuherlin Santa Moranie; Ir. Aqwam Rosadi Kardian, MM (Jurnal Sistem Informasi, 2002)
The use of servers in local network systems is very important, as the networkmanagement, database storage and other resource companies which are used togetherin a local network system. Local network system design based on user needs,technologies and resources used.